P16 expression and clinicopathological features of oral and oropharyngeal squamous cell carcinoma - Raphael, Rosemary; V., Priya P.; K., Anju C.; S., Sankar (International Journal of Research in Medical Sciences, 2021)
Background: There is an epidemiological shift in head and neck squamous cell carcinoma (HNSCC) attributable to HPV infection. HPV positive HNSCC has unique biology, risk factors, clinicopathological characteristics and outcome. There is a large variation in the published prevalence of HPV-related HNSCCs in India ranging from 7 to 78.7%. This study aims to find the P16 expression in the oral cavity and oropharyngeal SCC, thereby prevalence of HPV in our setting and to define the clinicopathological characteristics of HPV positive tumours in our setting. Methods: 210 specimens of primary Oral squamous cell carcinoma (OSCC) and Oropharyngeal Squamous cell carcinoma (OPSCC) were included. Immunohistochemistry was done using monoclonal mouse p16 antibody. Clinical details of each case were collected. Analysis was done using SPSS software and the association of P16 and clinicopathological variables were calculated using Fishers exact test. Results: P16 positive expression is observed only in 1/122 (0.82%) of OSCC and 8/88 (9%) of OPSCC. P16 positivity showed significant association with Grade of tumor (p= 0.008) and histological variant of SCC (p=0.00). 77.7% of P16 positive tumours are Grade 2 and 66.6% of Basaloid SCC was P16 positive. There is no significant association between p16 expression and other variables (subsite, age, gender, alcoholism, smoking, betel chewing and stage). Conclusions: P16 positivity was higher in oropharyngeal than in oral cancer. However, the HPV positivity rates are lower than other parts of India.